Mycobacterium tuberculosis and M. bovis BCG Moreau Fumarate Reductase Operons Produce Different Polypeptides That May Be Related to Non-canonical Functions - Schwarz, Marcos Gustavo Araujo; Antunes, Deborah; Corrêa, Paloma Rezende; Silva-Gonçalves, Antônio José da; Malaga, Wladimir; Caffarena, Ernesto Raul; Guilhot, Christophe; Mendonça-Lima, Leila (Frontiers in Microbiology, 2021)
Tuberculosis is a world widespread disease, caused by Mycobacterium tuberculosis (M.tb). Although considered an obligate aerobe, this organism can resist life-limiting conditions such as microaerophily mainly due to its set of enzymes responsible for energy production and coenzyme restoration under these conditions. One of these enzymes is fumarate reductase, an heterotetrameric complex composed of a catalytic (FrdA), an iron-sulfur cluster (FrdB) and two transmembrane (FrdC and FrdD) subunits involved in anaerobic respiration and important for the maintenance of membrane potential. In this work, aiming to further characterize this enzyme function in mycobacteria, we analyzed the expression of FrdB-containing proteins in M.tb and M. bovis BCG Moreau, the Brazilian vaccine strain against tuberculosis. We identified three isoforms in both mycobacteria, two of them corresponding to the predicted coded polypeptides of M.tb (27 kDa) and BCG Moreau (40 kDa) frd sequences, as due to an insertion on the latter’s operon a fused FrdBC protein is expected. The third 52 kDa band can be explained by a transcriptional slippage event, typically occurring when mutation arises in a repetitive region within a coding sequence, thought to reduce its impact allowing the production of both native and variant forms. Comparative modeling of the M.tb and BCG Moreau predicted protein complexes allowed the detection of subtle overall differences, showing a high degree of structure and maybe functional resemblance among them. Axenic growth and macrophage infection assays show that the frd locus is important for proper bacterial development in both scenarios, and that both M.tb’s and BCG Moreau’s alleles can partially revert the hampered phenotype of the knockout strain. Altogether, our results show that the frdABCD operon of Mycobacteria may have evolved to possess other yet non-described functions, such as those necessary during aerobic logarithmic growth and early-stage steps of infection.